Safety and Outcomes of Ipsilateral Antegrade Angioplasty for Femoropopliteal Disease. (February 2018) - Cragg, James; Lowry, Danielle; Hopkins, Jonathan; Parker, David; Kay, Mark; Duddy, Martin; Tiwari, Alok
Purpose: Previous reports have suggested higher periprocedural complications after ipsilateral antegrade femoral arterial access (AA). We looked at a contemporary series comparing complication rates between AA and contralateral retrograde femoral arterial access (RA) for femoropopliteal angioplasty. Method: A prospective review of all cases between 2010 and 2015 in a United Kingdom tertiary vascular center. Demographical and procedural data were obtained for those undergoing percutaneous femoropopliteal angioplasty. The primary outcome looked at periprocedural complications including retroperitoneal hematoma, pseudoaneurysm, hematoma requiring transfusion, arteriovenous fistulation, and surgical intervention. Secondary outcomes included contrast and radiation doses in addition to procedural failure leading to major amputation. Results: A total of 556 (66% male) patients underwent femoropopliteal angioplasty, 461 (82%) via AA. Groups were of comparable age, sex, comorbidity, and symptomatology. AA patients had a lower body mass index, 26 versus 29 ( P = .005). No significant difference was seen in periprocedural (15.8% AA vs 11.6% RA; P = 0.292) or access site complications (3.7% AA vs 1.1% RA; P = 0.186). There was less need for a closure device, 40.3% AA vs 73% RA ( P < .01), less contrast, 94 mL AA: 114 mL RA ( P < .001), and less radiation, 3487 cGy cm 2 AA: 9697 cGy cm 2 RA ( P < .001). Arterial access was also associated with greater technical success of 83.8%: 73.3% RA ( P = .002). Conclusions: Arterial access is associated with higher technical success and reduced contrast/radiation doses with no significant difference in complications compared to RA contrary to previous reports.